Naming, Defining, Phrasing Strong Asymmetrical Dependencies A Textual Approach - Bischoff, Jeannine; Conermann, Stephan; Gymnich, Marion (Dependency and Slavery Studies, 2023)
The eleven contributions in the volume examine the terminology used to refer to enslaved people and people in other forms of strong asymmetrical dependency as well as narratives by means of which dependency has been either justified or challenged. The articles address a wide range of historical contexts - from medieval Scandinavia and the Fatimid Empire to the history of abolition in Martinique and human rights violations in contemporary society.